Leading Employees Through the Crises: Key Competences of Crises Management in Healthcare Facilities in Coronavirus Pandemic - Jankelová N; Joniaková Z; Blštáková J; Skorková Z; Procházková K (Dove Medical Press, 2021)
Nadežda Jankelová, Zuzana Joniaková, Jana Blštáková, Zuzana Skorková, Katarína ProcházkováDepartment of Management, Faculty of Business Management, University of Economics in Bratislava, Bratislava, SlovakiaCorrespondence: Nadežda JankelováDepartment of Management, Faculty of Business Management, University of Economics in Bratislava, Dolnozemská Cesta 1, Bratislava, 852 35, SlovakiaTel +421 911 232 927Email nadezda.jankelova@euba.skPurpose: The fast and shocking onset of the crisis caused by the COVID-19 virus created the need for a complete crisis management of healthcare facilities to manage the current stage of the crisis. The purpose of our research is to examine the relations between the competences of crisis management in healthcare facilities and the performance of employees, measured during the acute stage of the crisis by their feeling of satisfaction, safety and creation of conditions for work, whereby we assume that these variables are mutually interlinked by the sharing of information, teamwork and cognitive diversity of the work teams.Materials and Methods: A questionnaire survey was created and used based on a sample of 216 mid-level managers of health care facilities in Slovakia, which took place during the first month after the outbreak of the crisis (during the month of March/April 2020). The Baron and Kenny mediator model has been used for research purposes and the Freedman–Schatzkin test has been used to test the mediator effect. Regression analysis has been used to verify the hypotheses. The control variables were the size of the healthcare facility based on the number of employees, gender and age of the manager, his position in the management hierarchy and the duration of practice in a management position. The ANOVA analysis of variance was used to analyze multiple dependencies. The level of significance was 5%. The research sample consisted of 216 managers at different types of healthcare facilities.Results: The hypothesis for the dependency between the crisis competences of management and performance of teams during the acute stage of the crisis, facilitated by sharing information, teamwork and cognitive diversity of crisis management was confirmed. It is a multilateral incomplete mediation, where almost two thirds of the total effect are facilitated by mediators, of which the sharing of information has the greatest effect (35%).Conclusion: Based on our mediation model, healthcare facilities, which strive to implement crisis management during the acute stage of the crisis, should place emphasis especially on reliable background information and the fast sharing of information, supporting the performance of healthcare teams. The strategies for achieving these goals should also include education focused on the development of managerial competences.Keywords: crisis management, sharing information, teamwork, team performance, cognitive diversity